DIFFERENTIATING THE POPULATION OF SILKWORM BUTTERFLIES BY LIFE EXPECTANCY (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The topic describes the selection of the silkworm and its role in the development of the industry, the favorable object of the silkworm in breeding work, the correlation of the main economic valuable characters with the life expectancy of female butterflies, the activity of especially biological indicators and conclusions.